2019
DOI: 10.1044/2019_ajslp-19-0034
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Clinicians With Specialization in Childhood Apraxia of Speech

Abstract: Purpose Little is known about how clinicians develop expertise in childhood apraxia of speech (CAS), a rare speech disorder with heterogeneous presentation. The purpose of this survey study was to examine the beliefs and practices of clinicians specializing in CAS. Method Speech-language pathologists who self-identify as having expertise in CAS ( n = 165) completed an online survey regarding influences on clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Although the diagnostic features of both CAS and childhood dysarthria are reasonably well documented, speechlanguage pathologists report diagnostic uncertainty, having low confidence in diagnosing these conditions [5••]. For example, Randazzo [52] reported that clinicians with specialist CAS practice in the United States were confident in diagnosing standalone CAS in children; however, they felt less comfortable in diagnosis where a child may have either multiple speech disorders or other non-speech conditions. This diagnostic uncertainty can be seen in the research literature and clinically in labels such as "suspected CAS" (e.g.…”
Section: Confidence In Motor Speech Diagnosismentioning
confidence: 99%
“…Although the diagnostic features of both CAS and childhood dysarthria are reasonably well documented, speechlanguage pathologists report diagnostic uncertainty, having low confidence in diagnosing these conditions [5••]. For example, Randazzo [52] reported that clinicians with specialist CAS practice in the United States were confident in diagnosing standalone CAS in children; however, they felt less comfortable in diagnosis where a child may have either multiple speech disorders or other non-speech conditions. This diagnostic uncertainty can be seen in the research literature and clinically in labels such as "suspected CAS" (e.g.…”
Section: Confidence In Motor Speech Diagnosismentioning
confidence: 99%
“…Obtaining information from clinicians using surveys is one direct method to achieve these goals. Information about clinical practice with English speakers who have CAS has been obtained from SLPs via survey with respect to diagnostic criteria [49] and clinical management [50,51], as well as the development of expertise [52]. These survey studies have provided the basis for further investigation of specific topics.…”
Section: Importance Of Survey Studiesmentioning
confidence: 99%
“…This underscores the need for investigation of the effectiveness of available evidence-based treatment programs in real clinical settings. Randazzo [52] suggested that clinicians develop their CAS expertise mainly based on continuing education programs. This drew attention to the content of these profit-making courses.…”
Section: Importance Of Survey Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent genome research offers multiple new gene variants associated with the disorder (Hildebrand et al, 2020), few known or putative causal genes have been identified to date (Carrigg et al, 2016;Peter et al, 2016). A second approach is to examine the trajectory of speech sound development across time for infants later identified with CAS (Highman et al, 2008), an approach that is of interest to clinicians (Randazzo, 2019) and has the potential to assist in the very early detection of the disorder (Allison et al, 2020). This approach to the study of CAS could open new paths of treatment techniques, much like increased inquiry into the developmental trajectory of disorders such as ASD, Fragile X syndrome, and Rett syndrome led to suggestions for their early identification and, in the case of ASD, subsequent toddler treatment protocols.…”
Section: Early Detection Of Casmentioning
confidence: 99%